Analisis Pengendalian Kualitas Sablon Pada Sandal Jepit Dengan Menggunakan Statistical Process Control (SPC) di PT. XZ - Ruspendi, Ruspendi; Mashabai, Ismi; Sarwoko, Wanto; Rusmalah, Rusmalah; Bayu, Sella (Industrika : Jurnal Ilmiah Teknik Industri, 2025)
PT. XZ is a company engaged in the manufacture of flip-flops. One of the sandal products produced is Screen-printed flip flops. However, in every production process failure is inseparable in the form of defective products in the production process. The purpose of this research is to minimize defects in Screen printing products. To reduce these defects, it is necessary to analyze the production process using the Statistical Process Control method. The analysis was carried out by using Seven Tools and 5W+1H tools. The results of the analysis show that the types of defects that occur in Screen printing products are the color of the paint is uneven, the paint is smeared and peeled off, and the Screen printing is not precise. Based on the three types of defects, the most dominant defect is uneven paint color with a percentage of 41,8%. Screen printing product defects are caused by human, machine, material, and method. Improvement efforts made to minimize the occurrence of uneven/fading paint color defects, namely conducting briefings and conducting supervision and checking on Screen printing results, checking on the Screen before printing is done, checking paint before printing, and providing training on rework standardization to employees and conducting regular performance evalutions. Keywords: Quality, Statistical Process Control, Seven Tools, 5W+1H